Static critical behavior of the ferromagnetic transition in La0.67Ba0.33–xZnxMnO3 manganites. (3rd June 2017) - Zaidi, Asma; Mohamed, Zaineb; Dhahri, Ahmed; Dhahri, J; Hlil, E.K.; Alharbi, T.; Zaidi, M.; Alzubaidi, S.
ABSTRACT: The critical properties of perovskite manganite La0.67 Ba0.33 − x Zn x MnO3 around the paramagnetic–ferromagnetic phase transition are investigated through various techniques such as modified Arrott plot, Kouvel-Fisher method and critical isotherm analysis. Through the nature of this transition was found to be in second order. The value of critical exponent, derived from the magnetic data using the Kouvel-Fisher method, yields0.356 ± 0.004 ≤ β ≤ 0.367 ± 0.006, 1.252 ± 0.005 ≤ γ ≤ 1.293 ± 0.022 and 4.60± 0.03≤ δ ≤ 4.66 ± 0.06 with a T C of 259.98 ± 0.32 − 221.73 ± 0.05 K. The exponent values are close to those expected for three-dimensional Heisenberg ferromagnets with short-range magnetic interaction.